The killing days - Pervanić, Kemal, 1968- (London : Blake, 1999)
Paddy Ashdon: Foreword -- Brian Phillips: Preface -- Prologue -- Part one: the attack -- Part two: Omarska -- Part three: Manjaca.
Keywords: Pervanić, Kemal, -- 1968-; Omarska (Concentration camp); Manjača (Concentration camp); Yugoslav War, 1991-1995 -- Prisoners and prisons, Serbian; Yugoslav War, 1991-1995 -- Personal narratives, Bosnian; Yugoslav War, 1991-1995 -- Bosnia and Herzegovina -- Prijedor Region; Concentration camp inmates -- Bosnia and Herzegovina -- Biography; Prijedor Region (Bosnia and Herzegovina) -- Biography